Penerapan Automatic Drip Irrigation System (ADIS) berbasis Internet Of Things (IoT) untuk Monitoring dan Meningkatkan Produktivitas Cabai - Samsu, L.M.; Yahya; Nurhidayati (Fakultas Teknik Universitas Hamzanwadi, 2025)
Padamara Village is one of the villages in Sukamulia District with the largest agricultural expanse reaching 155 Ha, of which 90% is a productive area in the first and second planting seasons after rice. The cayenne pepper plant is a plant that is suitable for cultivation in highland and lowland areas. The optimal growth and yield of cayenne pepper plants is very dependent on adequate soil quality, proper watering management and fertilizer application. Checking soil conditions is very important for the growth of cayenne pepper plants which have optimal humidity of 50%-70% so that they are not too dry or wet with a soil pH of 6-7 and a temperature of 24-28 degrees Celsius. The